The reason for God : belief in an age of skepticism - Keller, Timothy, 1950-2023. (New York : Dutton, 2008)
Although a vocal minority continues to attack religious faith, for most Americans, faith is a large part of their lives: 86% of Americans refer to themselves as religious, and 75% of all Americans consider themselves Christians. So how should they respond to these passionate, learned, and persuasive books that promote science and secularism over religion and faith? For years, Tim Keller has compiled a list of the most frequently voiced "doubts" skeptics bring to his Manhattan church; here, he dismantles each of them. Written with atheists, agnostics, and skeptics in mind, Keller also provides an intelligent platform on which true believers can stand their ground when bombarded by the backlash. This book challenges such ideology at its core and points to the true path and purpose of Christianity.--From publisher description.
The leap of doubt -- There can't be just one true religion -- How could a good God allow suffering? -- Christianity is a strait jacket -- The church is responsible for so much injustice -- How can a loving God send people to hell? -- Science has disproved Christianity -- You can't take the Bible literally -- Intermission -- The reasons for faith -- The clues of God -- The knowledge of God -- The problem of sin -- Religion and the Gospel -- The (true) story of the cross -- The reality of the Resurrection -- The dance of God -- Epilogue: Where do we go from here?
Includes bibliographical references (p. 243-281) and index.
Keywords: Apologetics; Faith; Skepticism